Colorectal cancer survival among Malaysia population: data from the Malaysian National Cancer Registry - Muhamad, Nor Asiah; Ma’amor, Nur Hasnah; Rosli, Izzah Athirah; Leman, Fatin Norhasny; Abdul Mutalip, Mohd Hatta; Chan, Huan-Keat; Yusof, Siti Norbayah; Tamin, Nor Saleha Ibrahim; Aris, Tahir; Lai, Nai Ming; Abu Hassan, Muhammad Radzi (Frontiers in Oncology, 2023)
Background: Colorectal cancer (CRC) is a major cause of cancer-related mortality worldwide. It is the second leading cause of cancer death in men and women in Malaysia and poses a major burden on society. Aims: To determine the overall survival rate of patients diagnosed with CRC and factors contributing to survival. Methods: Data was obtained from the Malaysia National Cancer Registry. We identified all patients with CRC and screened a total of 15,515 patients. We included a total of 5,675 CRC patients from 1st January 2012 to 31st December 2016. Sex, age groups, ethnic groups, stage at diagnosis, cancer sites and status of treatment received were analysed. Kaplan-Meier analysis was performed to estimate the 1-, 3- and 5-year survival of CRC. The log-rank test was conducted to compare the survival between sex, age groups, ethnic groups, stage at diagnosis, cancer sites and status of treatment received. Multiple Cox regression was conducted to determine the risk of CRC death. Results: Of 5,675, a total of 2,055 had died, while 3,534 were censored and another 86 were still alive within five years of CRC diagnosis. The 1-, 3- and 5-year survival rates were 68.5%, 34.7%, and 18.4% respectively with median survival time of 24 months. Significant differences in survival rates of CRC were observed between age groups (p<0.001), ethnic groups (p<0.001), stages at diagnosis (p<0.001), treatment status (p=0.003) and treatment modalities (p<0.001). No significant difference was observed in survival rates of CRC between sex (p=0.235) and cancer sites (p=0.410). Those who were 80 years old and above was found to be at higher risk of CRC death compared to those below 80 years old (adjusted HR: 1.24, 95% CI 1.14 – 1.36). The risk of CRC death was also found four times higher among those with stage IV compared to those in stage 0 (adjusted HR: 4.28, 95% CI 3.26 – 5.62). Conclusion: In general, Malaysian patients with CRC had low survival rates. National health policies should focus on enhancing awareness of CRC, encouraging early screening and developing strategies for early detection and management to reduce CRC-associated mortality.